Self-Reported Value of Spiritual Issues among Adolescent Psychiatric Inpatients - Grossoehme, Daniel H. (The Journal of pastoral care, 2001)
Reports on a survey of a prospective, uncontrolled sample of adolescent psychiatric inpatients on the importance of spiritual issues to them. Results indicated that the vast majority of adolescents in this sample indicated that spiritual beliefs are considered important. Notes that a majority reported that mental health professionals rarely asked them about their beliefs in the spiritual areas. Observes that nearly all the patients reported having a chaplain-led spiritual group that they perceived as a helpful part of the therapeutic milieu.